(60-2x)(80-2x)=800

Simple and best practice solution for (60-2x)(80-2x)=800 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (60-2x)(80-2x)=800 equation:


Simplifying
(60 + -2x)(80 + -2x) = 800

Multiply (60 + -2x) * (80 + -2x)
(60(80 + -2x) + -2x * (80 + -2x)) = 800
((80 * 60 + -2x * 60) + -2x * (80 + -2x)) = 800
((4800 + -120x) + -2x * (80 + -2x)) = 800
(4800 + -120x + (80 * -2x + -2x * -2x)) = 800
(4800 + -120x + (-160x + 4x2)) = 800

Combine like terms: -120x + -160x = -280x
(4800 + -280x + 4x2) = 800

Solving
4800 + -280x + 4x2 = 800

Solving for variable 'x'.

Reorder the terms:
4800 + -800 + -280x + 4x2 = 800 + -800

Combine like terms: 4800 + -800 = 4000
4000 + -280x + 4x2 = 800 + -800

Combine like terms: 800 + -800 = 0
4000 + -280x + 4x2 = 0

Factor out the Greatest Common Factor (GCF), '4'.
4(1000 + -70x + x2) = 0

Factor a trinomial.
4((20 + -1x)(50 + -1x)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(20 + -1x)' equal to zero and attempt to solve: Simplifying 20 + -1x = 0 Solving 20 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -1x = 0 + -20 Combine like terms: 20 + -20 = 0 0 + -1x = 0 + -20 -1x = 0 + -20 Combine like terms: 0 + -20 = -20 -1x = -20 Divide each side by '-1'. x = 20 Simplifying x = 20

Subproblem 2

Set the factor '(50 + -1x)' equal to zero and attempt to solve: Simplifying 50 + -1x = 0 Solving 50 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-50' to each side of the equation. 50 + -50 + -1x = 0 + -50 Combine like terms: 50 + -50 = 0 0 + -1x = 0 + -50 -1x = 0 + -50 Combine like terms: 0 + -50 = -50 -1x = -50 Divide each side by '-1'. x = 50 Simplifying x = 50

Solution

x = {20, 50}

See similar equations:

| 12x^3-x^2-20x=0 | | 8n^2+10n+5=0 | | 3x^2=6-5 | | v=ir | | C(m)=0.15m+0.75 | | 3=8-4X | | 5x+18=12x-45 | | 8x-6=6x+12 | | 25x+4-5=0 | | .375x+x=99 | | 0976+645=66 | | (18+2)*(x-4)=(x*x)-(32*32) | | 45-5h=5(9-h) | | 5-3(b-8)=9(b+2)+1 | | 8-3x-x^2=0 | | 69(x+2)=18 | | 23-14x=9 | | ln(4x-7)=0 | | 3(y-6)=4y-8 | | 8x+3y+4=0 | | 4-2x=x+16 | | 10x-7y=-20 | | 88-38=5.6(h-4) | | p-38=5.6(20-4) | | p-38=5.6(18-4) | | 4x-2x=-12 | | 25-(3x+2x)=10 | | 16x=32 | | 10x-6=64 | | 3x^2+21x+30= | | -y+18+3y=6+5y | | 4y-3=75-x |

Equations solver categories